2014
DOI: 10.1111/mmi.12855
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis protein CT009 is a structural and functional homolog to the key morphogenesis component RodZ and interacts with division septal plane localized MreB

Abstract: Summary Cell division in Chlamydiae is poorly understood as apparent homologs to most conserved bacterial cell division proteins are lacking and presence of elongation (rod shape) associated proteins indicate non-canonical mechanisms may be employed. The rod-shape determining protein MreB has been proposed as playing a unique role in chlamydial cell division. In other organisms, MreB is part of an elongation complex that requires RodZ for proper function. A recent study reported that the protein encoded by ORF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 68 publications
6
31
1
Order By: Relevance
“…As seen in Figure 1, we observed using super-resolution structured illumination microscopy (SIM) the polar localization of the major outer membrane protein (MOMP) in the budding daughter cell as previously reported(7). Consistent with its proposed role in division(8), MreB_6xH was localized in a band-like structure across the septum and not in puncta as previously reported(13, 16). Interestingly, when 3D reconstructions were assembled from the SIM images, we observed that MreB_6xH formed ring-like structures at the septum with areas of more intense signal (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As seen in Figure 1, we observed using super-resolution structured illumination microscopy (SIM) the polar localization of the major outer membrane protein (MOMP) in the budding daughter cell as previously reported(7). Consistent with its proposed role in division(8), MreB_6xH was localized in a band-like structure across the septum and not in puncta as previously reported(13, 16). Interestingly, when 3D reconstructions were assembled from the SIM images, we observed that MreB_6xH formed ring-like structures at the septum with areas of more intense signal (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Given our hypothesis for the role of chlamydial MreB in directing polarized division, we examined its localization during the first division of an RB. We were unable to detect endogenous MreB with the antibody previously used to image the distribution of MreB in Chlamydia (13). We then attempted to image wild-type and various truncation mutants of MreB using a GFP sandwich (SW) fusion strategy that, in E. coli , was reported to be functional(14) (N-or C-terminal fluorescent protein fusions with MreB display an artifactual localization(15)).…”
Section: Resultsmentioning
confidence: 88%
“…Chlamydiales are amongst the few known bacteria that lack FtsZ, the bacterial tubulin homolog that organizes the divisome complex at midcell to direct septal peptidoglycan synthesis and facilitates cytokinesis (Busiek and Margolin, 2015). Evidence has been provided that the bacterial actin complex, composed of MreB actin and its regulator RodZ, partially substitute for the role of FtsZ in cytokinesis and spatial regulation of septal peptidoglycan synthesis Kemege et al, 2015;Liechti et al, 2016). After a complete replication cycle re-differentiation into elementary bodies takes place in response to unknown signals, and new elementary bodies are released from the cell by either lysis or extrusion.…”
Section: Chlamydialesmentioning
confidence: 99%
“…This led to the model that peptidoglycan synthesis may drive cytokinesis in this organism (88). Indeed, in C. trachomatis and a related organism, MreB and RodZ (9), which are involved in spatially regulating peptidoglycan incorporation, localize to cell division sites (65, 71, 87). Interestingly, recent observations have suggested that, even in E. coli , FtsZ may not provide the force for membrane invagination and constriction during cell division and that peptidoglycan assembly may instead be the rate-limiting step that deforms the membrane (142), suggesting that cell wall-driven cytokinesis may be a widely conserved mechanism driving bacterial cell division.…”
Section: Introductionmentioning
confidence: 99%